Studi Literatur Penggunaan Internet of Things (IoT) dalam Sektor Kesehatan - Dhoni Setyanto; Puji Laksmini (Pusat Riset dan Inovasi Nasional, 2025)
The reality of the aging process in humans, the shortage of healthcare resources, and the increasing cost of medical care make Internet of Things (IoT)-based technologies need to be adapted to address these challenges in healthcare. IoT can lead to a wide range of medical applications, including remote health monitoring, fitness programs, chronic diseases, and elderly care. Another important potential application is sensitivity to home care and medication and by healthcare providers. This article aims to provide a description of the use of IoT in the health sector through the presentation of examples of IoT applied in the world of health from previous research. The research method used is literature search from various journals, books, and other e-resources. The result is an overview of the use of IoT in the health sector through the presentation of existing examples.